1994
DOI: 10.1016/0370-2693(94)90564-9
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical meson-baryon dynamics from large-Nc QCD

Abstract: The large-N c limit of the meson-baryon effective Lagrangian is shown to reduce to a semiclassical field theory. A chiral bag structure emerges naturally in the N c → ∞ limit.A possible connection between the chiral bag picture and the Skyrme model is discussed.The classical meson-baryon theory is used to reproduce the M 3 π non-analytic correction to the baryon mass obtained previously as a loop correction in chiral perturbation theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
4
20
0
Order By: Relevance
“…The pion mass is known to change slightly as density increases, so putting into Eq. (12) the empirical value obtained from π-mesic atoms [17], m ⋆ π (ρ 0 )/m π ≈ 1.05, one obtains (11). Since the coupling g ω related to the hidden gauge coupling g does not scale at mean field [1,5], this result immediately implies that at…”
Section: Linking Chiral and Walecka Mean Fieldsmentioning
confidence: 74%
“…The pion mass is known to change slightly as density increases, so putting into Eq. (12) the empirical value obtained from π-mesic atoms [17], m ⋆ π (ρ 0 )/m π ≈ 1.05, one obtains (11). Since the coupling g ω related to the hidden gauge coupling g does not scale at mean field [1,5], this result immediately implies that at…”
Section: Linking Chiral and Walecka Mean Fieldsmentioning
confidence: 74%
“…One should be able to obtain the leading in 1/N c contributions from classical field theory. For example, it was shown that the N c m 3/2 q oneloop correction to the baryon mass could be obtained from the energy of the pion cloud coupled to a classical baryon source [19]. The term in Eq.…”
Section: Large-nmentioning
confidence: 99%
“…Nevertheless, the N C counting rules outlined above apply generally, not just in solitonic theories, and one could look into their consequences for theories coupling external baryons to pions . This in fact has been accomplished [28], [29]. The picture that emerges is the following: Suppose one starts with a meson-baryon lagrangian of the form L = L M + L M B where the subscripts denote the purely mesonic part and the meson baryon interactions, and wherein the baryon has been introduced as an external field and provided L M supports a stable soliton, then the leading O(N C ) of this solitonic theory corresponds to the set of all multi loop graphs without a closed meson loop generated from L and evaluated in the limit of a static baryon.…”
Section: The Skyrme Modelmentioning
confidence: 99%
“…The part proportional to the divergent λ may formally be expanded According to (2.27) the divergencies in (2.25) may finally be absorbed into a redefinition of the lagrangians LECs. The total soliton mass (tree + 1-loop) is obtained as 28) where E cas represents the Casimir energy (2.26) and…”
Section: Continuum Contributions: the Phaseshift Formulamentioning
confidence: 99%